Lessons From Systemic Bank Restructing. (Economic Issues; Economic Issues ;, 1998)
Systemic bank restructing aims to improve bank performance - that is, restore solvency and profitability, improve the banking system's capacity to provide financial intermediation between savers and borrowers, and restore public confidence. The authors of this studyanalyzed the experiences of 24 countries that initiated reforms in the1980s and early 1990s.